2009
DOI: 10.1128/aem.00875-09
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cinnamon Oil on icaA Expression and Biofilm Formation by Staphylococcus epidermidis

Abstract: Staphylococcus epidermidis is notorious for its biofilm formation on medical devices, and novel approaches to prevent and kill S. epidermidis biofilms are desired. In this study, the effect of cinnamon oil on planktonic and biofilm cultures of clinical S. epidermidis isolates was evaluated. Initially, susceptibility to cinnamon oil in planktonic cultures was compared to the commonly used antimicrobial agents chlorhexidine, triclosan, and gentamicin. The MIC of cinnamon oil, defined as the lowest concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
92
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(103 citation statements)
references
References 39 publications
4
92
1
2
Order By: Relevance
“…The results showed that all six oral spray formulations significantly inhibited biofilm formation and disrupted the biofilm structure. This result is similar to the study by Nuryastuti et al who studied the inhibitory effects of cinnamon oil on Staphylococcus epidermidis biofilm 26 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results showed that all six oral spray formulations significantly inhibited biofilm formation and disrupted the biofilm structure. This result is similar to the study by Nuryastuti et al who studied the inhibitory effects of cinnamon oil on Staphylococcus epidermidis biofilm 26 .…”
Section: Discussionsupporting
confidence: 92%
“…There are many possibilities to demonstrate varying sensitivities with different strains of S. mutans. Also, different oil formulations resulted in different levels of genes expression leading to differences in aciduric and biofilm formation 12,[24][25][26] . This study also tested the inhibitory effect on growth and biofilm formation of S. mutans (ATCC 25175).…”
Section: Discussionmentioning
confidence: 99%
“…Different methods for assessing Candida biofilm formation have been reported in the literature (Krom et al 2007, Pierce et al 2008. In this study, colorimetric evaluation showed that the absorbance readings were proportional to cell density of the biofilm in agreement with Krom et al (2007) and Nuryastuti et al (2009). Small variations in the metabolic activities of the biofilm formed on the polystyrene surface were detected between the C. parapsilosis complex isolates tested.…”
Section: Discussionsupporting
confidence: 75%
“…Standard cell suspensions [100 µL of a suspension containing 1 × 10 6 cells/mL in Roswell Park Memorial Institute (RPMI) 1640 supplemented with Lglutamine and buffered with 0.165 M morpholinepropanesulfonic acid (MOPS) (Sigma)] were seeded in selected wells and incubated for a series of time intervals (4,6,8,12,18,24,36,48,72,84 and 96 h) at 37ºC. A semi-quantitative measure of the formed biofilms was calculated using a 2,3-bis (2-methoxy-4-nitro-5-sulphophenyl)-2-H-tetrazolium-5-carboxanilide (MTT) (Sigma) reduction assay (Berridge et al 2005, Krom et al 2007, Nuryastuti et al 2009). MTT solution (20 µL) [a stock solution containing 5 mg of MTT per mL of phosphate buffered saline (PBS)] was added to each well and the samples were incubated at 37ºC for 6 h. After staining, plates were washed three times with PBS.…”
Section: Methodsmentioning
confidence: 99%
“…From a molecular perspective, the cinnamon components destroy the cytoplasmic membrane of Gram‐positive and Gram‐negative bacteria and induce the depletion of intracellular ATP concentrations. The aqueous extract of cinnamon is also known to have antibacterial effects against Helicobacter pylori (Nuryastuti et al., 2009). Furthermore, the MIC values decreased significantly ( p  <   0.05) as the pH decreased.…”
Section: Resultsmentioning
confidence: 99%